Social media marketing strategies and their impact on customer loyalty - Alazzaz, Abrar Abdullah (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to analyze social media marketing strategies and their impact on customer loyalty among companies in Kuwait. The descriptive-analytical approach was used, and a questionnaire was employed to collect data from a sample of company employees. The results indicate a statistically significant positive relationship between social media marketing strategies and customer loyalty, highlighting the importance of investing in these strategies to enhance customer relationships and achieve marketing success.